The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/sle.0b013e3181a4d0e1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Closed-suction Drain in Preperitoneal Space on the Incidence of Seroma Formation After Laparoscopic Total Extraperitoneal Inguinal Hernia Repair

Abstract: Drain after TEP significantly reduces the incidence of seroma formation without increasing the risk of infection or recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 19 publications
2
56
0
Order By: Relevance
“…Seroma is a common post-LIHR complication, which has an incidence between 1.9% and 22.9%. 10 This complication is mainly caused by the secretions of the excluded distal hernia sac after hernia sac transection or the residual accumulated liquid in the empty cavity after hernia content reduction. Seroma has a high incidence among patients with a long-term adhesive hernia sac as well as with a large scrotal hernia.…”
Section: Discussionmentioning
confidence: 99%
“…Seroma is a common post-LIHR complication, which has an incidence between 1.9% and 22.9%. 10 This complication is mainly caused by the secretions of the excluded distal hernia sac after hernia sac transection or the residual accumulated liquid in the empty cavity after hernia content reduction. Seroma has a high incidence among patients with a long-term adhesive hernia sac as well as with a large scrotal hernia.…”
Section: Discussionmentioning
confidence: 99%
“…The drain was also placed in patients on antiplatelet therapy. Some previous studies have demonstrated that use of closed suction drainage in TEP hernia repair led to a significant decrease in seroma formation without any increase in the risk of infection or recurrence [29].…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to reduce the occurrence of seroma formation have included closed suction drainage of the preperitoneal space [3] or tacking the loose TF to the pubic ramus [4]. Both of these techniques are not without problems, as they can create extra discomfort to the patient, potentially increase the risk of infection, and also lead to chronic pubic bone pain from the tack staples or vasculo-nervous injury if Wxing the TF to the abdominal wall.…”
Section: Introductionmentioning
confidence: 98%